Skin bacterial volatiles: propelling the future of vector control. Issue 1 (January 2022) - Lucas-Barbosa, Dani; DeGennaro, Matthew; Mathis, Alexander; Verhulst, Niels O.
Abstract : The skin microbiota plays an essential role in the protection against pathogens. It is our skin microbiota that makes us smell different from each other, rendering us more or less attractive to mosquitoes. Mosquitoes exploit skin bacterial odours to locate their hosts and are vectors of pathogens that can cause severe diseases such as malaria and dengue fever. A novel solution for long-lasting protection against insect vectors of disease could be attained by manipulating the bacterial commensals on human skin. The current options for protection against biting insects usually require topical application of repellents that evaporate within hours. We discuss possible routes for the use of commensal bacteria to create a microbial-based repellent. Highlights: Skin microorganisms produce odours that female mosquitoes use to locate their hosts. Efforts should be undertaken to correlate the human microbiome signature more comprehensively with the human odour signature. Manipulation of the human skin microbiome is already a possibility, and recent developments have opened exciting new paths to address a varied number of skin conditions. The next step is to manipulate skin bacteria for the control of disease vectors. We envisage the development of probiotics rich in bacterial strains characteristic of poorly attractive individuals, increasing skin microbial diversity, or bioengineering microbes to reduce persons' attractiveness to mosquitoes.